IVF in Sri Lanka: A concise history of regulatory impasse - Simpson, Bob (Reprod Biomed Soc Online, 2016)
This article outlines the development of IVF in Sri Lanka from the first successful births in the late 1990s and over the subsequent 15 years. It is based on anthropological fieldwork carried out at various points during this period. The piece focuses on the challenges entailed in achieving regulation of the new reproductive technologies against a backdrop of: (i) a bitter civil war; (ii) a complex mosaic of different religious traditions (specifically, Buddhism, Catholicism, Hinduism and Islam); and (iii) a shift towards neo-liberal marketization, particularly in relation to specialist and hi-tech medical interventions. The article concludes that ‘soft’ regulation operates both to avoid conflict around highly contentious issues in debates about reproductive rights as well as to enable commercially driven developments in technologically specialised areas of medicine.